Dochody w Nigerii według wysokości - Vielrose, Egon (Wydział Prawa i Administracji UAM, 1975)
The author has analysed the level and distribution of personal income. I. e. he has stated that the coefficient of income concentration amounts to 0,47; in the urban and rural areas, however, the coefficient mentioned is silightly lower.
Distribution of Personal Income in Nigeria